2015
DOI: 10.1016/j.biomaterials.2015.02.118
|View full text |Cite
|
Sign up to set email alerts
|

Food-associated stimuli enhance barrier properties of gastrointestinal mucus

Abstract: Orally delivered drugs and nutrients must diffuse through mucus to enter the circulatory system, but the barrier properties of mucus and their modulation by physiological factors are generally poorly characterized. The main objective of this study was to examine the impact of physicochemical changes occurring upon food ingestion on gastrointestinal (GI) mucus barrier properties. Lipids representative of postprandial intestinal contents enhanced mucus barriers, as indicated by a 10 – 142-fold reduction in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 46 publications
1
59
0
Order By: Relevance
“…There are six cell-bound mucins that are known to be present in the GI tract, MUC1, MUC3, MUC4, MUC12, MUC13 and MUC17 [37]. The thickness and composition of the loose layers have shown to be dependent on the diet of the subject [68]. Since this mucus layer is focused on coating and lubricating undigested material, it protects the firmly bound layer through the peristaltic motion in the GI tract [55,66].…”
Section: The Oral Route: Physiology and Immunologymentioning
confidence: 99%
“…There are six cell-bound mucins that are known to be present in the GI tract, MUC1, MUC3, MUC4, MUC12, MUC13 and MUC17 [37]. The thickness and composition of the loose layers have shown to be dependent on the diet of the subject [68]. Since this mucus layer is focused on coating and lubricating undigested material, it protects the firmly bound layer through the peristaltic motion in the GI tract [55,66].…”
Section: The Oral Route: Physiology and Immunologymentioning
confidence: 99%
“…However, a change in size of this magnitude would not account for the measured impact of lipids on particle transport through mucus, and the moderate decrease in zeta potential observed in simulated fed state medium would not be expected to hinder transport. 18 …”
Section: Resultsmentioning
confidence: 99%
“…We recently demonstrated that food associated lipids representative of postprandial intestinal contents altered mucus barrier properties, as indicated by a 10 – 142-fold reduction in the transport rate of 200 nm microspheres through mucus, depending on their surface chemistry. 18 The mechanism and role of potential interactions between exogenous lipids and mucus, however, remain unclear. For example, it is not certain whether the bile salt micelles present in fed state intestinal contents stay intact within mucus.…”
Section: Introductionmentioning
confidence: 99%
“…The particles used in MPT studies can represent drug carriers or drug particles, and as such, this technique provides direct information related to penetration of drug carriers through mucus barriers. The particle surface properties (e.g., chemistry and charge) and particle size can be varied to reveal the significance of these parameters on transport through the mucus barrier[59]. One advantage to carrying out MPT studies on native collected mucus, as opposed to cell cultures or excised tissue as described below, is the relative ease of focusing on the particles within a thick (e.g., ~1 mm) mucus gel layer, without concern about whether the particles being imaged are within mucus as opposed to the fluid above or cells below the mucus layer.…”
Section: Isolated Mucus Modelsmentioning
confidence: 99%